Method of calculation of asymmetry of bar push from chest according to the results of high-speed 3D shooting - Khasin, L. A.; Drozdov, A. L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and test a methodology for analyzing the asymmetry of the push of the barbell from the chest.